Electro-sorption of ammonium by a modified membrane capacitive deionization unit - Sakar, Hacer; Celik, Isil; Canbolat, Cigdem Balcik; Keskinler, Bülent; Karagündüz, Ahmet (Taylor & Francis Inc, 2017)
A modified membrane capacitive deionization (MCDI) unit with additional flow channels in the anode and cathode chambers was used to study the performance of ammonium ion removal. The influences of operating parameters including initial ammonium concentration, flow rate and applied potential and the effect of flow in the anode and cathode chambers were investigated. Flow through the anode and cathode chambers significantly enhanced the electro-sorption efficiency. The electro-sorption of ammonium at 5 mL/min was about 65% greater than without flow.
Keywords: Electro-sorption; flow chambers; membrane capacitive deionization